MATERNAL KNOWLEDGE OF WHO GUIDELINES FOR TREATMENT OF ACUTE RESPIRATORY INFECTIONS IN CHILDREN UNDER FIVE IN PAKISTAN - Shaikh, Beenish Tahir; Wasim, Shehnaz; Yasin, Hafsa; Khalid, Sidra; Masood, Malick Muhammed Sabih (Journal of Ayub Medical College Abbottabad, 2019)
Background: Acute Respiratory Infections (ARIs) are among the leading causes of morbidity and mortality in children under the age of five in Pakistan. Gauging the knowledge and practices of mothers related to ARIs may hold a key role in reducing the incidence and complications. Our study assessed the knowledge of mothers regarding ARIs among children under five years in accordance with WHO guidelines, and its association with education and socioeconomic status of mothers. In addition, we studied the association between education of mothers and socioeconomic status with vaccination status of child. Methods: This cross-sectional study was conducted from May to December 2016 at Civil Hospital, Ziauddin Hospital and Gulshan-e-Sikanderabad PHC Karachi and involved mothers with at least one child under the age of five years. Four hundred mothers were interviewed using a questionnaire. Results were analysed using SPSS 20.0. Results: 51% of mothers were found to have an above average understanding about ARIs with a mean score of 13.35±3.03 out of a possible 20. There is no association between knowledge of mothers and their level of education. Education level of the mother was found to have a significant association with the vaccination status of youngest child. Mothers having no education or just religious education had the highest percentages of incomplete vaccinations. Conclusion: Most mothers had above average knowledge of what classified as an ARI and could identify the danger signs. Uneducated mothers had incomplete vaccinations of their youngest child. The majority of mothers had satisfactory breastfeeding habits. Keywords: Acute Respiratory Infection, Maternal, Knowledge, WHO Guidelines, Children under five, Management of ARI, Vaccination, Breastfeeding, Self-medication, Pakistan